Moonlight influence on quality of nestlings of scops owls depends on paternal coloration. (24th December 2021) - Avilés, Jesús M; Cruz-Miralles, Ángel; Parejo, Deseada
Abstract: Lunar phases might favor the maintenance of color polymorphism via disruptive selection if the different color variants performed differently in terms of prey capture under different moonlight levels. Moonlight, however, may affect prey capture as a side effect of its influence on prey behavior. Here we combine data of parental provisioning and quality of owlets with one ex-situ study of grasshopper activity to test whether Eurasian scops owls ( Otus scops ) with different plumage color and their prey are differently affected by moonlight. Food provisioning increased from new- to full-moon. However, the effect of moonlight on owlet mass gain and immune response depended on paternal coloration. On the one hand, body mass gain of nestlings of the greyest fathers increased from nights with new- to full-moon, whereas it did not change with moonlight for the brownest fathers. On the other hand, PHA response of nestlings of the brownest fathers increased with high moonlight levels during the first week of life, whereas it did not change with moonlight levels for the greyest fathers. Grasshoppers were more active at new moon than at full or waning moon. Our study provides supporting evidence that moonlight influences the behavior of both scops owls and its prey and suggests that fluctuations in environmental conditions can modulate the advantages of morphs. These results are important because they provide a general insight into a little appreciated mechanism for the maintenance of color polymorphism in natural populations based on the interactive effect of different environmental factors. Abstract : Moonlight favors different strategies of nestling care in brown and grey owls. Using data collected over four years, we found that body mass gain of nestlings of the greyest fathers increased from nights with new- to full-moon, and that the immunology of nestlings of the brownest fathers increased with high moonlight levels during the first week of life.